LncRNA SUMO1P3 regulates the invasion, migration and cell cycle of gastric cancer cells through Wnt/β-catenin signaling pathway. (2nd November 2021) - Xu, Zhong; Ran, Jing; Gong, Kai; Hou, Yihan; Li, Ji; Guo, Yijuan
Abstract: Objective: To investigate the regulatory effect of long non-coding RNA (lncRNA) SUMO1P3 on invasion, migration and cell cycle of gastric cancer (GC) cells through Wnt/β-catenin signaling pathway. Methods: Tumor tissues and adjacent normal tissues from the GC patients were collected, and human normal gastric epithelial cells GES1 and GC cells SGC-7901, MKN45, HGC-27 and AGS were selected for study. The expression of SUMO1P3 in GC tissues and cells were detected by RT-qPCR. The effects of SUMO1P3 on the proliferation, invasion and migration of SGC-7901 and MKN45 cells were detected by CCK-8, transwell and wound healing assay respectively, and the effects of SUMO1P3 on apoptosis and cycle progression of SGC-7901 and MKN45 cells were detected by flow cytometry. The expressions of Wnt/β-catenin pathway-related and cell cycle-related proteins were detected by Western blot. Results: The expression of SUMO1P3 was significantly upregulated in GC tissues and cell lines. Downregulation of SUMO1P3 significantly inhibited the SGC-7901 and MKN45 cell proliferation, invasion, migration, and cycle progression and promoted the cell apoptosis, while overexpression of SUMO1P3 showed the opposite effect. Further study showed that downregulation of SUMO1P3 significantly reduced the expressions of Wnt1, β-catenin, c-myc, and Cyclin D1 in SGC-7901 and MKN45 cells. Conclusion: SUMO1P3 may promote invasion, migration, and cycle progression of SGC-7901 and MKN45 cells by enhancing the Wnt/β-catenin pathway.